Laut yang Tak (Lagi) Bersahabat: Adaptasi Nelayan Terhadap Perubahan Iklim di Desa Rampa Kabupaten Kotabaru - Aldi Ansara; Ismar Hamid (Prodi Sosiologi FISIP ULM, 2023)
Fishermen in Rampa Village Kotabaru District are faced with serious problems in conducting fishing activities due to climate change. This study aims to describe the existence of local wisdom and forms of adaptation of fishermen in dealing with climate change. This study uses a qualitative approach to the type of phenomenological research. Data collection techniques using participant observation, in-depth interviews and documentation. The data analysis technique uses the interactive model's Miles and Huberman, which consists of data reduction, data display, and conclusion/verification. The results show that the local knowledge of fishermen from Rampa Village that had existed for a long time was still being used, even though in some aspects it had been made adaptation to faced changes in environmental conditions due to climate change. The form of adaptation is that fishermen no longer go to sea based on the seasonal calendar but based on the latest weather conditions. Fishing equipment used it has changed as a form of technological adaptation in faced climate change. The form of adaptation is that all fishing boats are equipped with engines to be more adaptive to sea conditions that can change suddenly, for example storms that come without being accompanied by natural signs which are usually a source of information for fishermen. In carrying out fishing activities, some fishermen already use a modern navigation system (GPS), which also functions to track fish spots in the sea. This means that the traditional fishing system is no longer effective. In terms of intensity, previously fishermen did not go to sea only on certain days (holidays and the likes). Currently, fishermen may not go to sea for a long time due to weather conditions that do not support fishing activities. This has an effect on the socio-economic life of the community, namely that people's income becomes erratic.